Adulticidal, larvicidal, pupicidal and oviposition deterrent activities of essential oil from Zanthoxylum limonella Alston (Rutaceae) against Aedes aegypti (L.) and Culex quinquefasciatus (Say) - Mayura Soonwera; Siriporn Phasomkusolsil (Asian Pacific Journal of Tropical Biomedicine, 2017)
Objective: To evaluate adulticidal, larvicidal and oviposition deterrent response of the essential oil from dried Zanthoxylum limonella (Z. limonella) fruit against Aedes aegypti (Ae. aegypti) and Culex quinquefasciatus (Cx. quinquefasciatus). Methods: Z. limonella oil was tested by biological assays at 1%, 5% and 10% concentrations in ethanol. Adulticidal efficacy was tested against the 2–3 day old adult females. Larvicidal activity was tested against immature stage of mosquitoes. Oviposition deterrence of the oil was evaluated on gravid females. Results: The adult mortality was observed after 24 h with the LC50 of 6.0% for Ae. aegypti, and 5.7% for Cx. quinquefasciatus. Larvicidal bioassay was carried out with the 10% Z. limonella oil against immature stages of Ae. aegypti and Cx. quinquefasciatus, which caused 100% mortality after 12 h and 24 h. In the larvicidal experiment, Z. limonella showed effective result at 1%, 5% and 10% concentrations with the values of LT50 Ae. aegypti = 9.78, 5.61, 0.24 h for larvae and LT50 = 64.08, 21.23 h for pupae; Cx. quinquefasciatus had LT50 = 28.46, 20.25, 1.01 h for larvae and LT50 = 67.52, 27.96, 4.11 h for pupae, respectively. Oviposition deterrence of the oil was evaluated on gravid females. In the study, 10% Z. limonella showed 100% repellency for Ae. aegypti and 99.53% for Cx. quinquefasciatus. Likewise, oviposition activity indexes of these oil concentrations were all negative values ranging from–0.89 to −1.00 for Ae. aegypti and–0.64 to–0.99 for Cx. quinquefasciatus. The oviposition activity indexes values revealed that Z. limonella oil has deterrent effect, and it caused a remarkable negative response resulting in very few eggs. Conclusions: This result indicates that Z. limonella oil can be used as an effective adulticide, larvicide and oviposition deterrent against Ae. aegypti and Cx. quinquefasciatus.